Respuesta :

cher
Equation 1)  y - 2x = 3
Equation 2)  3x - 2y = 5

Switch around x and y in equation 1.

1)  -2x + y = 3

2)  3x - 2y = 5

Multiply ALL of equation 1 by 2.

1)  2(-2x + y = 3)

Simplify.

1)  -4x + 2y = 6

2)  3x - 2y = 5

Add equations together.

-x = 11

Divide both sides by -1.

x = -11

Plug in -11 for x in the first equation.

-4x + 2y = 6

-4(-11) + 2y = 6

Simplify.

44 + 2y = 6

Subtract 44 from both sides.

2y = 6 - 44

Simplify.

2y = -38

Divide both sides by 2.

y = -38/2

y = -19

So, x = -11, y = -19

D : (-11, -19)

~Hope I helped!~